Conceptual stabilizer selection for nanomilling based on dispersibility parameters - Peppersack, C.; Flach, Frederik; Prziwara, P.; Damm, Cornelia; Breitung-Faes, S.; Peukert, Wolfgang; Kwade, A. (Advanced Powder Technology, 2023)
The choice of stabilizers to prevent particle agglomeration during nanomilling is an elaborate process which is often based on empirical rules and experience. Usually, extensive screening studies are required to find an appropriate stabilizing additive. The present study shows how the selection of polymeric stabilizers can be narrowed down to a couple of additives based on Hansen solubility parameters. The stabilizing capability was found to be a function of the difference between solubility parameters of additive and particulate species. Solubility parameters of different additives and two particle species were determined by inverse gas chromatography and the stabilization performance was evaluated by nanomilling experiments conducted with a stirred media mill. It is shown that a certain difference of solubility parameters between particle and additive is necessary in order to provide colloidal stability of small particles after milling. On the one hand, the additive needs a certain affinity to the particle surface, while on the other hand it also has to be compatible with the solvent. Based on experimental data, a solubility parameter difference in the range of 7.5–10 MPa0.5 was identified as a good measure for a proper stabilizer selection. The approach was proved for two organic particle species and represents a promising tool for a more efficient formulation development of drug nanosuspensions.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Colloidal stability; Hansen solubility parameter; Inverse gas chromatography; Nanomilling